1960
DOI: 10.1083/jcb.7.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Study of the Phagocytosis Process in Lung

Abstract: Diluted India ink was instilled into the nasal cavity of mice and the lungs of some animals were fixed with osmium tetroxide at various intervals after one instillation. The lungs of other animals were fixed after 4, 7, 9, 16, or 18 daily instillations.The India ink was found to be phagocytized almost exclusively by the free alveolar macrophages. A few particles are occasionally seen within thin portions of alveolar epithelium, within the "small" alveolar epithelial cells, or within occasional leukocytes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
30
1
1

Year Published

1961
1961
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(40 citation statements)
references
References 27 publications
8
30
1
1
Order By: Relevance
“…In this case the erythrocyte keeps almost the initial position. The above findings lead to a disagreement with reports which are supported by electron microscopic findings only, that a foreign body is trapped into the cytoplasm of cells by indentation, or invagination of the cell membrane.6),20), 23) It has been clarified that phagocytosis first requires the development of the pseudopod, and that it is greatly related with the adhesiveness and surface tension of the pseudopod.…”
contrasting
confidence: 52%
“…In this case the erythrocyte keeps almost the initial position. The above findings lead to a disagreement with reports which are supported by electron microscopic findings only, that a foreign body is trapped into the cytoplasm of cells by indentation, or invagination of the cell membrane.6),20), 23) It has been clarified that phagocytosis first requires the development of the pseudopod, and that it is greatly related with the adhesiveness and surface tension of the pseudopod.…”
contrasting
confidence: 52%
“…This has never been seen although some hundreds of sections have been studied. In addition, the cells do not resemble macrophages [Palade, 1956;Essner, 1960;Karrer, 1960], nor are they similar to any of the usual connective tissue cells. Altschul [1954] and other workers, whom he cites, are of the opinion that endothelial cells can turn into macrophages.…”
Section: Casley-smith 374mentioning
confidence: 97%
“…Other investigators showed that type I and type II cells take up ferritin and horseradish peroxidase into vesicles (47,98,123), whereas type II cells internalize SP-A from the alveolar space by receptormediated endocytosis (94). Both type I and type II cells have been shown to phagocytose foreign particles (22,54,63). Finally, clathrin-coated pits are present in alveolar type I and type II cells, whereas caveolincoated plasmalemmal vesicles (i.e., caveolae) are present in both pulmonary vessel endothelial cells and alveolar type I epithelial cells, suggesting possible transcytosis of proteins via these structural features (16,64,85).…”
Section: Pathways and Mechanisms Of Lung Protein Clearancementioning
confidence: 99%